2013
DOI: 10.4100/jhse.2013.8.proc3.21
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of visual strategy in elite and amateur handball goalkeepers

Abstract: Rivilla-García J, Muñoz A, Grande I, Sanchís, M, Sampedro J. A comparative analysis of visual strategy in elite and amateur handball goalkeepers. J. Hum. Sport Exerc. Vol.8, No. Proc3, pp. S743-S753, 2013. The aim of the present study was to analyze the visual strategies prior to a throw from 7 metres in elite and amateur handball goalkeepers. To this end we analyzed the visual fixations in number and order of 10 goalkeepers (29.7±5.4 years; 14.7±8.6 years of experience), 3 elite and 7 amateurs, during the lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…We use Hatzl's analysis (2000) of relevant body movements in handball, which found that the crucial factors are: 1) the direction of the ball and ball-carrying hand in the last stage of the throwing phase; 2) rotation of the hip and upper body around its longitudinal axis; 3) how far the ball is from the body (to the side) and 4) relative shoulder width as seen from the goalkeeper's perspective. These findings have been confirmed by using occlusion techniques (see below), eyemovement recordings and statistical analysis of variations in handball shots and their importance to differentiation of shot direction (Alhosseini, Safavi & Namazi, 2015;Rivilla-García et al, 2013;Bourne, Bennet, Hayes & Williams, 2011). More specifically, Hatzl empirically concluded that the most informative period, when the anticipation most likely happens, was between the defined turning point of the throwing motion (first body rotation) and the time when the ball-carrying hand and the head of the thrower make their last turns.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…We use Hatzl's analysis (2000) of relevant body movements in handball, which found that the crucial factors are: 1) the direction of the ball and ball-carrying hand in the last stage of the throwing phase; 2) rotation of the hip and upper body around its longitudinal axis; 3) how far the ball is from the body (to the side) and 4) relative shoulder width as seen from the goalkeeper's perspective. These findings have been confirmed by using occlusion techniques (see below), eyemovement recordings and statistical analysis of variations in handball shots and their importance to differentiation of shot direction (Alhosseini, Safavi & Namazi, 2015;Rivilla-García et al, 2013;Bourne, Bennet, Hayes & Williams, 2011). More specifically, Hatzl empirically concluded that the most informative period, when the anticipation most likely happens, was between the defined turning point of the throwing motion (first body rotation) and the time when the ball-carrying hand and the head of the thrower make their last turns.…”
Section: Introductionmentioning
confidence: 81%
“…Our sample is similar in size to those of other studies researching anticipation in handball: N = 20 in Alsharji (2014), N = 37 (14 experts and 23 non-experts) in , and N = 10 in Rivilla- García et al (2013). Since Loffing & Hageman used the most similar research method to the one we used, we relied on that study when conducting power analysis.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Specifically, expert athletes engage in more effective visual search strategies and focus on more relevant areas compared to less skilled athletes ( Williams et al, 1999 ). This behavior has been replicated in a wide variety of sports and tasks, including football ( Savelsbergh et al, 2002 ), tennis ( Murray and Hunfalvay, 2017 ), handball ( Rivilla-García et al, 2013 ), and volleyball ( Piras et al, 2014 ). Expert athletes have also been shown to be more accurate in decision-making and faster in anticipating future events compared to less skilled athletes ( Mann et al, 2007 ).…”
Section: Introductionmentioning
confidence: 83%
“…Studies conducted in experimental settings stated the medium speed of the throws during the 2013 Men's World Handball Championship reached 22 m/s (Cortés et al, 2017), and showed that goalkeepers initiated their movement while the thrower still had the ball in his hands, respectively 43 ms (as a mean) and 193 ± 67 ms before the release of the ball (Gutierrez-Davila et al, 2017). This strategy was related to visual and anticipatory strategies which aimed to perceive relevant features in a situation and to predict future actions based on the movement of other players to reduce uncertainty and timepressure (Debanne, 2003;Gutierrez-Davila et al, 2017;Rivilla-García et al, 2013).…”
Section: Introductionmentioning
confidence: 99%